ANALISIS PENILAIAN PRESTASI KERJA PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN BULUNGAN PROVINSI KALIMANTAN UTARA - patri juari; Ayu Widowati Johannes (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
This study discusses "analysis of Civil Servant Performance Appraisal in Human Resources Agency and Human Resource Development of Bulungan District of North Kalimantan Province". The purpose of this research is to know and analyze the implementation of Performance Appraisal of Civil Servants, to know and analyze the factors inhibiting the implementation of Performance Appraisal of Civil Servants Employment Agency and Human Resource Development District Bulungan Province of North Kalimantan. This research uses qualitative method by exposing explorative with inductive approach. With data collection techniques are interviews, observation and documentation.Based on the results of observations the author after applying the apprentices concluded that, the implementation of Performance Appraisals of Civil Servants in Human Resources Agency and Human Resource Development District Bulungan Province of North Kalimantan has been done. But there are obstacles, namely where the lack of understanding of a small part of civil servants about the procedure peyusunan Work Objectives Employees and Work Behavior. Recommended recommendations are to provide socialization and consultation with the right target, regarding the preparation of Employee Work Goals and Work Behavior to civil servants who do not understand about the regulation Keyword: Civil Servant, Performance Appraisal, Human Resources